Pengembangan Sistem Pemantauan Aktivitas Pengawasan Satpam dengan Proses Validasi Dinamis QR-Code pada Aplikasi Patrolee - Saputra, Laurentius Kuncoro Probo; Raharjo, Willy Sudiarto; Restyandito, Restyandito (STMIK Budi Darma, 2022)
Internet of Things (IoT) technology provides system integration to accelerate wireless remote data acquisition. This paper presents the implementation of IoT based applications to monitor security guard surveillance activities in the campus environment. The traditional reporting system still has many limitations. The security guard should make a written report to his supervisor and send the surveillance images using a third-party instant messaging application. The reporting results are not integrated. Implementation of IoT system which consists of Dynamic QR-code Display, Android Application, Web Application, and Cloud Database, enables the integration and real-time reporting system. Security guard reports can be seen directly, both written reports and the surveillance image, using a web application. Each security guard on duty has its unique QR code for each location and current surveillance schedule. It makes the security guard cannot ask their duties to other people. The results of this research show that this system has been able to meet the needs of security officers. The success rate of security guards when doing the task using this application is 90%.